Nowoczesne koncepcje rachunku kosztów i budżetowania w zakładach opieki zdrowotnej - Mazur, Iwona (Modern Concepts of Cost Accounting and Budgeting in Health Care Units, 2006)
The paper discusses the need for modification of both the cost accounting model currently applicable in the health care sector and the need for refining the process of budgeting. A concept which can successfully be implemented in health care facilities is presented and activity-based costing is discussed in more detail.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1103, s. 203-211